2004
DOI: 10.1016/j.rapm.2004.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of continuous femoral nerve block with nonstimulating catheter placement versus stimulating catheter-guided perineural placement in volunteers ,

Abstract: In this volunteer study, there was no statistically significant difference in block success between the two techniques. However, stimulating catheter-guided placement provided an increased overall quality of continuous femoral perineural blockade. Further studies are needed to verify these observations in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…Salinas et Al. in 2004(Salinas et al, 2004) published a prospective comparison of continuous femoral nerve block with nonstimulating catheter placement versus stimulating catheterguided perineural placement, randomizing twenty volunteers; a stimulating catheter was placed on one side and an identical non-stimulating catheter on the contralateral side. Success of femoral block was defined as loss of sensation to cold and pinprick stimuli.…”
Section: Study Description and Results (Table 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Salinas et Al. in 2004(Salinas et al, 2004) published a prospective comparison of continuous femoral nerve block with nonstimulating catheter placement versus stimulating catheterguided perineural placement, randomizing twenty volunteers; a stimulating catheter was placed on one side and an identical non-stimulating catheter on the contralateral side. Success of femoral block was defined as loss of sensation to cold and pinprick stimuli.…”
Section: Study Description and Results (Table 2 )mentioning
confidence: 99%
“…They concluded that blind catheter advancement was as reliable as a stimulating catheter technique for establishing and maintaining continuous femoral nerve block for postoperative analgesia as a part of multimodal analgesia technique after total knee arthroplasty. In summary, although advantageous from a theoretical standpoint and in experimental designs (Salinas et al, 2004), randomized controlled trials in the clinical environment have yielded limited evidence to justify use of stimulating catheters for continuous femoral nerve block after knee surgery. The increased cost and need for additional catheter adjustments compared with nonstimulating catheter also make it hard to justify their use in this clinical setting.…”
Section: Salinas Et Al 2004mentioning
confidence: 99%
“…Salinas et al, who also conducted a study of volunteers, reported that after an infusion of 0.2% ropivacaine at 10 mLÁhr -1 through a femoral catheter, a subsequent quadriceps motor block developed within five hours after an initial recovery. 25 The relation between prolonged sitting and increased numbness and pinprick sensation with subsequent motor block remains unclear. The additional nerve compression could have led to an additional effect on nerve conduction or produced a more ''toxic'' level of local anesthetic, leading to impaired sensory and motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no study has formally compared the equipment available for stimulating catheter insertion. RCTs have used alternately different kits: the Arrow StimuCath Continuous Nerve Block Set (Arrow international, Reading, PA, USA); [23][24][25]27 an 18G, 85-mm long needle, oversheathed with a plastic introducer set (Multiplex, Vygon, France); 28,29 a 50-mm, 18G needle with a stimulating catheter (Polymedic C-50 K +); 26 or a 22G, stimulating catheter with a 19.5G, 100-mm needle set (Stimulong Plus, Pajunk, Geisingen, Germany). 30 Further studies are required to compare the electrical properties of these kits.…”
Section: Discussionmentioning
confidence: 99%
“…in 20 healthy volunteers, Salinas et al 24 placed bilateral femoral catheters by randomizing one side to a non stimulating catheter and the contralateral side to a stimulating catheter (mean stimulation threshold of the catheter = 0.47 ± 0.05 mA; pulse width = 0.1 msec). Both catheters were bolused with 10 mL of lidocaine 1% and infused with ropivacaine 0.2% infusion (10 mL·hr -1 for four hours).…”
Section: Femoral Block (Fb)mentioning
confidence: 99%